Masticatory function in temporomandibular dysfunction patients: electromyographic evaluation Função mastigatória em pacientes com disfunção temporomandibular: avaliação eletromiográfica - Giédre Berretin-Felix; Katia Flores Genaro; Inge Elly Kiemle Trindade; Alceu Sergio Trindade Júnior (University of São Paulo, 2005)
Temporomandibular dysfunction (TMD) is a complex disturbance that involves the masticatory muscles and/or temporomandibular joint, causing damage to the masticatory function. This study evaluated the electromyographic activity of the masseter muscle during habitual mastication of bread, apple, banana, cashew nut and paraffin film (Parafilm M) in 25 adult subjects, of both gender, with TMD. The results were compared to those of a control group, composed of 15 adult subjects, of both sexes, free of signs and/or symptoms of TMD. The MYO-TRONICS Inc., K6-I computer software was used for electromyographic processing and analyzed the following parameters: duration of the act, duration of the masticatory cycle and number of cycles. No significant differences were found between subjects in the control group and individuals with TMD as to duration of the masticatory act and of the masticatory cycle, considering all materials used for mastication. The duration of the masticatory act and cycle was longer during mastication of paraffin film in both groups. The number of masticatory cycles was higher for mastication of apple in comparison to mastication of banana, in both groups. It can be concluded that the consistency of foods influences the duration parameters of the act, duration of the cycle and the number of masticatory cycles, and the behavior of the masticatory muscles in individuals with TMD during habitual mastication is similar to that verified in individuals without TMD. A disfunção temporomandibular (DTM) representa um quadro complexo que envolve os músculos mastigatórios e/ou a articulação temporomandibular, causando prejuízos à função mastigatória. Este estudo avaliou a atividade eletromiográfica do músculo masseter durante a mastigação habitual de pão, maçã, banana, castanha de caju e folha de parafilme (Parafilm M) em 25 indivíduos adultos, de ambos os gêneros, com DTM. Os resultados foram comparados com os obtidos para o grupo controle, composto por 15 indivíduos adultos, de ambos os gêneros, livres de sinais e/ou sintomas de DTM. Foi utilizado o programa computadorizado MYO-TRONICS Inc., K6-I no modo de processamento eletromiográfico, tendo sido analisados os seguintes parâmetros: duração do ato, duração do ciclo mastigatório e número de ciclos mastigatórios. Não foram encontradas diferenças estatisticamente significantes entre os indivíduos do grupo controle e com DTM no que diz respeito à duração do ato e do ciclo mastigatório, bem como o número de ciclos, considerando todos os materiais utlizados para a mastigação. A duração do ato e do ciclo mastigatório foi maior durante a mastigação de parafilme em ambos os grupos. O número de ciclos mastigatórios foi maior para a mastigação de maçã, em comparação à banana, nos diferentes grupos. Pode ser concluído que a consistência dos alimentos influencia a duração dos parâmetros duração do ato, duração do ciclo e número de ciclos mastigatórios e o comportamento dos músculos mastigatórios em indivíduos com DTM durante a mastigação habitual é semelhante à verificada em indivíduos sem disfunção.